PERAN MANAJEMEN SUMBERDAYA MANUSIA DI ERA DIGITAL - Nur Fadillah, Listiana; Jumrah, Jumrah; Kamarullah, Pratiwi; Veranita, Mira (ABISATYA DINAMIKA ISWARA, 2025)
Human Resource Management (HRM) plays a crucial role in helping organizations manage their workforce effectively to achieve their goals. In digital era, the role of HRM has expanded far beyond traditional administrative tasks. It has become a strategic partner focused on driving innovation, managing data, and building employees’ digital skills. Organizations are now expected to integrate digital technologies—such as Human Resource Information Systems (HRIS), artificial intelligence (AI), and various digital platforms—into key HR functions like recruitment, training, performance evaluation, and talent retention. This article explores the meaning and evolving role of HRM in the digital age through a qualitative, literature-based approach. The findings highlight that the success of HRM depends on how well organizations can adapt to technological change and foster a work culture that is flexible, collaborative, and data-driven. In this fast-paced, ever-changing environment, HRM plays a vital role in shaping resilient and competitive organizations